Perbedaan Kebocoran Tepi antara GIC Konvensional dan Resin Modified GIC pada Restorasi Kelas V (Difference on Microleakage of Conventional GIC and Resin Modified GIC in Class V Restoration) - Aditya Rama Devara; Cecilia G.J Lunardhi; Tamara Yuanita (Universitas Airlangga, 2016)
Background. Microleakage is one of the challenging concerns in direct filling restorations. Restoration material should have good adaptation between the restoration and the cavity walls to seal the cavity in a good way. Glass ionomer cement (GIC) is one of restoration material which indicated for class V cavity. GIC has a good adherence to the cavity wall but fragile to liquid contamination during the setting time. Resin modified glass ionomer cement (RMGIC) is a hybrid glass ionomer cement with the addition of hidroxyethylmethacrylate (HEMA) in the liquid to increase the properties and endurance to liquid contamination. Aim. The aim of this study was to investigate the difference on microleakage of conventional GIC and resin modified GIC in class V restoration. Material and methods. Class V cavities (depth: 2 mm) were prepared on the cervical surface of 32 human first permanent premolars. Teeth were classified into three groups. Group 1: conventional GIC + varnish. Group 2:RMGIC + varnish. All cavities were restored, then stored in artificial saliva at 37ºC for 24 hours. The teeth were immersed in a 1% methylene blue dye solution for 24 hours, and then rinsed in running water, dried, and sectioned longitudinally. The section were assessed for microleakage of dye penetration by two independent evaluators using a digital microscope. Data were collected and statistically analyzed. Results. RMGIC showed no significant difference with conventional GIC. However, there is a slight difference, RMGIC has a slight lower microleakage than conventional GIC. Conclusion. RMGIC showed only slight lower microleakage than conventional GIC, but not significant.